SUATU EKPLORASI EARNINGS MANAGEMENT SEBAGAI DAMPAK DARI PROFITABILITAS DAN UKURAN PERUSAHAAN DI INDONESIA DAN MALAYSIA - Jenny Sihombing (Fakultas Ekonomi Universitas Advent Indonesia, 2018)
This study is quantitative empirical evidence about how the effect of profitability and return on assets on earnings management, this study also examines whether company size can moderate the effect of profitability on return on assets. The findings of this study support the state-owned bank program that was formed into holdings, merger was carried out for the purpose of making banks in Indonesia bigger, stronger in competing with foreign banks, so that they would be more trusted and produce better levels of profitability. The results of this study also shown that banks with a large level of profitability tend to (although not significant) report that their operating profit smaller than they should to, in order to reduce tax liability and corporate social responsibility to the community. Other results from this study have also shown that larger bank significantly effect earnings management, that is by reporting bank profits that are greater than what actually happened. The purpose of the company to do such earnings management is to maintain, even to increase the credibility of the bank. It was required a better supervision from internal banks (including audit committees) also from external banks (by external auditors), so that the reported quality of earnings be better, yet the investors and creditors are more secure in placing every single money in the bank.